2022
DOI: 10.3390/vaccines10030361
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Guardians’ Intentions to Vaccinate Children against COVID-19

Abstract: A cross-sectional survey design was used to assess Arkansas parents’/guardians’ intentions to vaccinate their child against COVID-19. Parents/guardians whose oldest child was age 0–11 years (n = 171) or 12–17 years (n = 198) were recruited between 12 July and 30 July 2021 through random digit dialing. Among parents/guardians with an age-eligible child, age 12–17, 19% reported their child had been vaccinated, and 34% reported they would have their child vaccinated right away. Among parents/guardians with a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
5
12
1
Order By: Relevance
“…It has been identified that gender and educational level have a significant impact. Indeed, females and those with a lower educational level had a higher concern of side effects of the vaccination and this reflects the general trend in access to COVID-19 vaccine disparities that has been observed in several previous studies ( 33 37 ). The reason by which females are more concerned may be explained by the fact that in Italy they were more affected than men although male presented a higher risk of death ( 38 ).…”
Section: Discussionsupporting
confidence: 73%
“…It has been identified that gender and educational level have a significant impact. Indeed, females and those with a lower educational level had a higher concern of side effects of the vaccination and this reflects the general trend in access to COVID-19 vaccine disparities that has been observed in several previous studies ( 33 37 ). The reason by which females are more concerned may be explained by the fact that in Italy they were more affected than men although male presented a higher risk of death ( 38 ).…”
Section: Discussionsupporting
confidence: 73%
“…The results of the study are also consistent with the literature concerning vaccination against COVID-19 in children, which is crucial, considering that it effectively limits the need for hospitalization [49] but even about a quarter of parents declare that they would definitely not have their children vaccinated unless their school required it [50]. It has been established that individually targeted risk-oriented communication is crucial to achieve satisfactory results, but in adults the communicates concentrate on the risk of infecting others while in the case of children it may be more effective to focus on the risk resulting from the SARS-CoV-2 infection for themselves [51].…”
Section: Discussionsupporting
confidence: 86%
“…A preprint from Israel including parents with 5–11-year-old children, similar to our population, reported that 43% of these parents were hesitant to vaccinate their children ( 31 ). In July 2021, a small study conducted in Arkansas found that around 30% of parents will not vaccinate their children or only vaccinate them when required; interestingly, the hesitancy rates among parents of 12–18-year-old children were similar to the rate among parents with children younger than 12 years of age (28 and 27%, respectively) ( 32 ). Whereas recent studies from other countries found lower rates of vaccine hesitancy, studies from China, Vietnam, and Italy reported that about 26%, 21%, and 18% of parents were hesitant to vaccinate their 5–17-year-old, 3–17-year-old, and 12–18-year-old children, respectively ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%